Pengaruh Kecerdasan Emosi Dan Komitmen Organisasi Terhadap Kinerja Kolektor Koperasi Mori Sama Gowa - Rostini Rostini; Joko Purwanto; Syahribulan Syahribulan (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
The variables in this study are Emotional intelligence, Organizational Commitment and Collector Performance. Logic intelligence is an attempt to manage controlled logic and can be used to solve life problems. Organizational commitment that reflects some people recognizing and supporting the organization and performance represents quality and equal work results that can be achieved by an employee in carrying out tasks in accordance with the responsibilities given. This study uses a quantitative method, the subject of this research is 30 collectors, the sampling technique uses positive sampling data obtained by collecting research results questionnaires obtained from the hypothesis between X1 (Emotional Intelligence) on Employee Performance (Y) with a R value of 0,000 with the rules used P ≤ 0.05. So with the results of the hypothesis there is the influence of the emotional intelligence variable. The results obtained from the hypothesis between X2 (Organizational Commitment) on Employee Performance (Y) with a R value of 0,000 with the rule used P ≤ 0.05. So with the results of the hypothesis needed the influence of variables on the performance of collectors in the Mori Sama Gowa cooperative. Value is a quality and satisfying work that can be achieved by an employee in a job that is in accordance with the responsibility given to him based on the results performed can be seen in the appropriate table with a calculated F value of 11,650 with an F table of 3.39 and a significant value of 0.001 <0.05 <0.05 then H0 and H3 are accepted. Then it can be summarized here below below and below